A conceptual optimum design for a high-efficiency solar-assisted desalination system based on economic, exergy, energy, and environmental (4E) criteria. (August 2022) - Sohani, Ali; Delfani, Fatemeh; Fassadi Chimeh, Arash; Hoseinzadeh, Siamak; Panchal, Hitesh
Abstract: The goal of this study is to determine the optimum dimensions of an innovative high-efficiency solar still in a way that energy, exergy, environmental, and economic (4E) indicators are in the best condition at the same time. For this purpose, the annual yield (AYI) and the annual CO2 saving (ACDS) from the energy and environmental sides, as well as the annual average exergetic efficiency (AEXEF) and cost per liter (CPL) from the exergy and economic aspects, are considered as the objective functions of a multi-objective optimization (MOO). In addition, the impact of changing the inflation rate on the MOO results is found. The results demonstrate that compared to the base-case design, 508.2 L, 3.3%, and 101.1 g increase in AYI, AEXEF, and ACDS are achieved when MOO is applied, which shows 28.01, 5.56, and 28.01% enhancement, respectively. Moreover, CPL reaches from 0.0225 $.L −1 in the base-case design to 0.0178 $.L −1 for the optimal condition, which means 20.89% improvement. In addition, among the objective functions, by 22.89 and 3.09% changes within the range of 0.01 to 0.19, AYI and AEXEF are found as the most and least sensitive ones to inflation rate variation.